CASE REPORTSFenestrated stent graft in treatment of type IV thoracoabdominal aneurysm involving all visceral arteries - Majewski, Wacław; Juszkat, Robert; Stanisić, Michał; Kulesza, Jerzy; Majewska, Natalia; Perek, Bartłomiej; Oszkinis, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Conventional open surgical repair of thoracoabdominal aortic aneurysm (TAAA) is associated with high perioperative mortality and morbidity risk. Our report of successful treatment of a 56-year-old patient with TAAA involving all visceral arteries and with many comorbidities with a fenestrated stent graft supports its application in high-risk TAAA patients.